Responding to Heteronormativity: Lesbian, Gay, Bisexual and Asexual Preservice Teachers’ Dreams and Fears - Bower-Phipps, Laura (Current Issues in Education, 2020)
Heteronormativity, the “privileging of heterosexuality through its normalization” (Jackson, 2006, p. 109), causes confusion and anxiety for many lesbian, gay, bisexual, and asexual preservice teachers as they consider how they will talk about their lives with students. This article explores how preservice teachers have experienced the normalization of heterosexuality and the ways in which these experiences will shape their professional practices. Focus group and follow up interviews with lesbian, gay, bisexual, and asexual preservice teachers were analyzed using a constant comparison method. Findings suggest that participants’ professional vision was largely a response to heteronormativity. They wanted to be out, be role models, and create safe spaces; yet they felt unable to achieve this vision in what they perceived as heteronormative school climates. Implications for teacher preparation programs and policies include the importance of equipping all preservice teachers to identify and disrupt heteronormativity in schools.
Number: 1
Keywords: dept.cur; peer-reviewed; ⛔ No DOI found

The personal is professional: Unpacking cultural sanctions through the identities of mother /educator/lesbians - Bower-Phipps, Laura (Sexual Orientation and Teacher Identity: Professionalism and LGBTQ Politics in Teacher Preparation and Practice, 2019)
Keywords: dept.cur; dept.eng

Creating a Space for Teacher Candidates Committeed to Urban Settings: Action Research Program on the Urban Education Fellows Program - Bower-Phipps, Laura; Marx, H. A. (Teacher Education Yearbook XXIV: Establishing a Sense of Place for All Learners in 21st Century Classrooms and Schools, 2015)
The Association of Teacher Educators (ATE) Yearbook XXIV offers 16 captivating chapters related to establishing a sense of place or belonging for P-12 students, classroom teachers, teacher candidates, and teacher educators. The chapters include theory, research, concepts, principles, practices, and programs that inform and support as well as question and challenge readers from multiple perspectives. Readers gain insights and inspiration that illustrate ways teachers and learners negotiate meaning in environments where everyone experiences social and cultural connections with personal and academic fulfillment. Collectively, the authors identify, describe, analyze, and advance issues associated with creating both an individual and a shared sense of place among the ever-changing populations in contemporary P-12 schools and classrooms. Like human geographers, teacher educators and educational researchers study environments where children grow up and create bonds with their early environments that continue to influence them throughout their lives based on the ways in which meaning is negotiated in that early space. Candidates, teachers, and teacher educators benefit by investigating the presence and power of these landscapes impacting the teaching, learning, and schooling.
Google-Books-ID: 4bodCwAAQBAJ
Keywords: Education / Administration / General; Education / Educational Policy & Reform / General; Education / Inclusive Education; Education / Learning Styles; Education / Student Life & Student Affairs; dept.cur

Developing mentors: an analysis of shared mentoring practices - Bower-Phipps, Laura; Klecka, Cari Van Senus; Sature, Amanda L (The New Educator, 2016)
Understanding how experienced teachers share and articulate effective mentoring practices can guide efforts to prepare quality mentors. This qualitative study focused on mentoring practices within a teacher-designed student-teaching program conceptualized while the mentor teachers within the program were students in a graduate-level mentoring course and implemented upon the mentors’ completion of their graduate studies. Data sources included interviews and field notes from meetings with mentors and student teachers. The results detail specific mentoring practices: explicit instruction through scaffolding, developing the whole teacher, student-teacher-directed learning, fostering student teachers’ individual practice, explicit mentoring of one another, and reflecting on mentoring. These practices were enabled by program structures such as mentor meetings, an online forum, and mentors’ observation of all student teachers in the program. © 2016, © 2016 CCNY and ATE.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-875-982-659-553 tex.type: [object Object]
Keywords: dept.cur; peer-reviewed

Everyone has a story: A collaborative inquiry project by five teacher candidates of color and one white professor - Bower-Phipps, Laura; Tate, Rachel Watanabe; Mehta, Sejal; Sature, Amanda L (Current Issues in Education, 2013)
Initiatives to increase the number of teachers of color in U.S. public schools must be accompanied by culturally relevant teacher preparation for candidates of color. This study is a cooperative inquiry (Heron, 1996) conceived, conducted, and analyzed by five preservice teachers of color and one of their professors, a white lesbian. The women met biweekly for a year to co-construct meaning from their experiences in a teacher education program. They analyzed data sources together, including meeting transcripts, autobiographical sketches, and reflective writing on themes from the data. Key findings include the complexity of teacher candidates' identities; the importance of support systems for teacher candidates of color, particularly within predominantly white contexts; the connection between teacher candidates' backgrounds and their visions as teachers; and the role others' perceptions, particularly teacher educators, have played in teacher candidates becoming teachers.
Citation Key Alias: lens.org/033-975-273-700-369 tex.type: [object Object]
Keywords: Cooperative inquiry; Diversity; Teacher identity; Teachers of color; dept.cur; peer-reviewed; ⛔ No DOI found

Developing as Teachers and as Researchers: Emerging Professionals' Experiences with Cooperative Inquiry - Bower-Phipps, Laura; Cruz, Maria; Albaladejo, Cristina; Johnson, Arlette; Homa, Thomas (Networks: An Online Journal for Teacher Research, 2016)
This article details the second cycle of cooperative inquiry undertaken by emerging educators who self-identify as "other" because of gender, language, ethnicity, and/or sexual orientation. The current cycle focuses on the impact participation in cooperative inquiry had on researchers' teaching practices. Data sources include transcripts of group discussions and reflective writing completed six months, eighteen months, and two years after the completion of the first cycle of cooperative inquiry. Findings suggest that as a result of engagement in cooperative inquiry, the teacher/researchers established practices to decrease isolation, build unity, and understand students' backgrounds. Teacher/researchers viewed themselves as advocates for diversity within the classroom, took a collaborative approach to teaching, and came to see research as an essential element of effective teaching.
ERIC Number: EJ1152312
Keywords: Beginning Teachers; Cooperation; Educational Practices; Elementary School Teachers; Inquiry; Minority Group Teachers; Preservice Teachers; Self Concept; Social Distance; Student Teachers; Teacher Educators; Teacher Researchers; dept.cur